Coproduction of a resource sharing public views of health inequalities: An example of inclusive public and patient involvement and engagement - Charlotte Parbery‐Clark; Rosemary Nicholls; Lorraine McSweeney; Sarah Sowden; Joanne Lally (Health Expectations)
Abstract Background UNderstanding Factors that explain Avoidable hospital admission Inequalities—Research study (UNFAIR) addresses how to reduce health inequalities, particularly for avoidable hospital admissions. Our Patient and Public Involvement and Engagement (PPIE) members broached that health inequalities are complex, challenging to understand and communicate. They identified a need to explore diverse views, including people who have a higher risk of health inequalities. With limited public‐facing resources relating to the public's understanding or emotions around health inequalities, this project aimed to fill this gap using co‐leadership and co‐production. Methods Members of the public worked with researchers to co‐produce and run PPIE workshops. This project was co‐led by a member of the public and a researcher. One online workshop open to anyone in England accompanied by three face‐to‐face workshops were held. Public contributors, including people living in diverse communities, were invited. Inclusive involvement opportunities were offered including flexible ways of involvement and remuneration. To strengthen the key messages' rigour, transcriptions of the audio‐recordings from each workshop, with facilitator notes, were analysed using thematic analysis. From the key messages, an animation was co‐produced with public contributors with the public's voice being integral throughout. Key Messages A total of 58 people took part capturing intersecting and multiple dimensions of marginalisation including people with a range of ages, genders, ethnicities, socioeconomic backgrounds, and members of communities who face exclusion (including people with learning difficulties and experiencing ill‐health). The animation highlighted powerful lived experience, for example, some people are dying earlier than expected. Health inequalities conjured up powerful emotions, such as anger and hopelessness. Public views of how to address health inequalities included respecting, accepting and valuing everyone, regardless of, for example, where people live. The animation is publicly available for use by anyone, including decision makers across the health and care system. Conclusions Through co‐leadership and co‐production, this project is an example of inclusive PPIE. This project provided a way for the public's voice to influence policy and practice to inform understanding and action to address health inequalities. The animation provides powerful insights into what health inequalities mean to people with examples of lived experience and corroborates the moral argument for action by decision makers. Patient and Public Contribution Members of the public, including people who were affected or at higher risk of health inequalities, co‐led this project and were involved as co‐creators and developers from the inception of the project to completion. Their involvement was integral and documented in full throughout the project.